2005
DOI: 10.1097/01.mpg.0000182010.77322.de
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Steroid Treatment on Memory, Executive Function, and Mood in Pediatric Inflammatory Bowel Disease

Abstract: Background: Although IgA endomysial antibodies (EMA) and tissue transglutaminase (TG) are sensitive and specific serologic tests for the diagnosis of celiac disease, there is limited information on the association of the magnitude of antibody level with the severity of the histological abnormalities of the intestine. Purpose: To determine if EMA and TG titers correlate with the severity of histological changes in patients with celiac disease. Methods: We identified 148 children from our laboratory database tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Thus, the Somatic Complaints factor may be related, in part, to the autoimmune response observed during an active IBD flare. Second, study findings are consistent with a subset of symptoms commonly induced by exogenous steroids or cytokine (interferon) treatments in various human diseases [10, 33, 34]. In other words, the Somatic Complaints factor observed in this sample might, in part, reflect symptoms in response to common treatments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, the Somatic Complaints factor may be related, in part, to the autoimmune response observed during an active IBD flare. Second, study findings are consistent with a subset of symptoms commonly induced by exogenous steroids or cytokine (interferon) treatments in various human diseases [10, 33, 34]. In other words, the Somatic Complaints factor observed in this sample might, in part, reflect symptoms in response to common treatments.…”
Section: Discussionsupporting
confidence: 80%
“…Such sickness behaviors closely mirror symptoms of depression and often reflect non-gastrointestinal specific somatic complaints that are common secondary symptoms of IBD. Steroid-induced depression, which includes a number of the above symptoms in addition to irritability, has been reported in a number of physically ill populations [9], including youths with IBD [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Two studies investigating the effects of steroids on mood and memory in children with IBD found that those on steroids had significantly more problems with memory and depression compared with children not on steroids [20,21]. Mixed results have been found for the relationship between age at diagnosis and behavioral/emotional symptoms, with one study reporting worse outcomes for those diagnosed in adolescence [5,16 ] and one finding no developmental difference [16 ].…”
Section: Behavioral/emotional Functioningmentioning
confidence: 96%
“…Other risk factors that have been investigated include stressful life events, maternal depression, family dysfunction, and steroid treatment, and all have been found to be associated with increased depression symptoms [5,6,20,21]. Two studies investigating the effects of steroids on mood and memory in children with IBD found that those on steroids had significantly more problems with memory and depression compared with children not on steroids [20,21].…”
Section: Behavioral/emotional Functioningmentioning
confidence: 98%
“…Corticosteroids are the mainstay of treatment for acute exacerbations in children; however, they are ineffective in maintaining remission [40]. In addition, although their chronic use is limited by severe side effects (e.g., moon face/acne, weight gain/redistribution, bone demineralisation, delayed puberty, mood swings, high blood pressure, altered glucose metabolism) [41,42], patients often receive many rounds of steroid therapy. Tung et al evaluated the 1-year outcomes of corticoid therapy in paediatric CD as part of the population-based Olmsted County study [43].…”
Section: Treatment Options In Paediatric CDmentioning
confidence: 99%